Investor Reaction to Mandatory Offers on the Warsaw Stock Exchange - Szymon Okoń (Contemporary Economics, 2012)
The following paper aims to assess investor reaction to mandatory offers on the Warsaw Stock Exchange, which is important because knowledge about these reactions can be used to make better investment decisions. This paper highlights the importance of procedure in making a mandatory offer and its grounds in the Polish legal system. Additionally, it presents empirical research on the reactions of investors to mandatory offers on the Warsaw Stock Exchange. It has been provided that mandatory offers have a significant impact on the price of a company's shares listed on the Warsaw Stock Exchange. Knowledge about the reactions of investors to a mandatory offer may be used when selecting securities for an investment portfolio. The findings may provide guidance in deciding whether to begin or end investment in the company, both for individual and institutional investors. The event study methodology approach used in the paper is regarded as valuable and can be the basis for further research in other areas of the capital market research, especially in the context of information efficiency.
Keywords: G14; 330; mandatory offer; event study; investors'reactions